Contemporary Society of Eastern Java's Horseshoe: A Field Study of Valley and Coastal Community Civilization - Depict Pristine Adi; Enok Maryani; Mamat Ruhimat; Kokom Komalasari (Fenomena, 2026)
This study examines the social, cultural, and economic dynamics of communities in the East Java Horseshoe region, encompassing both valley and coastal areas. Previous research has rarely examined the interrelations among these communities, particularly in the context of globalization and modernization, underscoring the need for this study. The purpose of this research is to identify differences in lifestyle, interaction, and economic interdependence between agrarian, collective-based valley communities and coastal communities that are more receptive to modernization. Using a qualitative ethnographic approach, data were collected through participatory observation, in-depth interviews, and documentation, and analyzed descriptively and interpretively. The findings reveal fundamental differences: coastal communities demonstrate openness to modern technology, while valley communities preserve traditional values, and both are bound by reciprocal economic dependence in the trade of agricultural and marine products. These findings highlight the necessity of a valley–coastal synergy to support sustainable development. Practical recommendations include developing ecotourism grounded in local wisdom, providing cultural education for younger generations, and conserving the environment through prudent resource management. This research contributes strategically to local policy-making and serves as a reference for understanding community adaptation to global changes. Penelitian ini mengkaji dinamika sosial, budaya, dan ekonomi masyarakat di wilayah Tapalkuda Jawa Timur, yang mencakup kawasan lembah dan pesisir. Penelitian sebelumnya jarang mengkaji keterkaitan di antara masyarakat-masyarakat ini, terutama dalam konteks globalisasi dan modernisasi, sehingga menyoroti pentingnya penelitian ini. Tujuan penelitian ini adalah untuk mengidentifikasi perbedaan dalam gaya hidup, interaksi, dan saling ketergantungan ekonomi antara komunitas lembah berbasis agraris dan kolektif dengan komunitas pesisir yang lebih terbuka terhadap modernisasi. Dengan menggunakan pendekatan etnografi kualitatif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi, serta dianalisis secara deskriptif dan interpretatif. Temuan-temuan tersebut mengungkap perbedaan mendasar: masyarakat pesisir menunjukkan keterbukaan terhadap teknologi modern, sementara masyarakat lembah mempertahankan nilai-nilai tradisional, dan keduanya terikat oleh ketergantungan ekonomi timbal balik dalam perdagangan produk pertanian dan hasil laut. Temuan-temuan ini menyoroti pentingnya sinergi antara lembah dan pesisir untuk mendukung pembangunan berkelanjutan. Rekomendasi praktis meliputi pengembangan ekowisata yang berakar pada kearifan lokal, penyediaan pendidikan budaya bagi generasi muda, serta pelestarian lingkungan melalui pengelolaan sumber daya yang bijaksana. Penelitian ini memberikan kontribusi strategis bagi pembentukan kebijakan lokal dan berfungsi sebagai acuan untuk memahami adaptasi masyarakat terhadap perubahan global.